Parental Parenting Styles, Social Media, and Peer Influence on Sexual Behavior among Adolescents - Laili, Anis Nur; Wigati, Puspita Zella; Purwanti, Dwi; Sulistiyowati, Nur Indah; Esyuananik, Esyuananik (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Adolescence is a phase marked by curiosity and attraction to the opposite sex, which may influence their sexual behavior. According to BKKBN data from 2023, 60% of adolescents aged 16–17 years and 20% aged 14–15 years have engaged in sexual intercourse. A preliminary study at SMAN 1 Blega revealed that among 15 dating students, 4 reported kissing and petting. This study aimed to analyze the influence of parenting patterns, social media, and peer relationships on adolescent sexual behavior at SMAN 1 Blega. Using an analytical cross-sectional approach, the study surveyed 121 out of 158 grade 11 students through simple random sampling. Data analysis employed descriptive statistics, Spearman rank, and logistic regression. The findings indicated significant partial influences of authoritarian parenting (p=0.027; R²=0.208), non-risky social media access (p=0.002; R²=0.292), and peer influence (p=0.011; R²=0.256) on adolescent sexual behavior. Recommendations include replicating planned Generation (GenRe) and counseling teachers are advised to activate the Reproductive Health Information and Counseling Centers (PIK-R)programs tailored for adolescents and strengthening parental communication and supervision to mitigate risky sexual behaviors.